2003
DOI: 10.1002/macp.200390103
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrins in Polymer Synthesis: Free Radical Polymerization of β‐Cyclodextrin Complexes of Photosensitive Mesoionic 6‐Oxo‐1,6‐dihydropyrimidin‐3‐ium‐4‐olates in Aqueous Medium

Abstract: Solid mesoionic 2‐[2‐(isopropenylcarbonyloxy)ethylthio]‐1‐methyl‐6‐oxo‐3‐phenyl‐5‐propyl‐1,6‐dihydropyrimidin‐3‐ium‐4‐olate was complexed in water using β‐cyclodextrin (β‐CD) and randomly methylated β‐CD, which resulted in polymerizable complexes with 2:1 stoichiometry. The β‐CD complex was characterized using 1H NMR, ROESY NMR and UV spectroscopy. Polymerization of the complex prepared from methylated β‐CD led to a photosensitive polymer, which precipitated during polymerization and was nearly free of CD. Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The hydrophobic cavity of CDs binds suitable organics by hydrophobic interactions and/or H-bonds, while the hydrophilic outer shell provides the water solubility. Ritter et al successfully polymerized various hydrophobic monomers, such as styrene [33][34][35][36][37][38], (meth)acrylates [33,34,[39][40][41][42][43][44], phenol derivatives [45,46], fumarates [47,48], dienes [49,50], halo-olefins [51][52][53], and other non-commercial ones [54][55][56][57][58][59][60][61] in water, solubilized by CD, via free radical polymerization methods. During the polymerization, the CD, every time, slips off from the last monomeric unit of the polymer, and the product precipitates, resulting in a pure product, or simple purification.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophobic cavity of CDs binds suitable organics by hydrophobic interactions and/or H-bonds, while the hydrophilic outer shell provides the water solubility. Ritter et al successfully polymerized various hydrophobic monomers, such as styrene [33][34][35][36][37][38], (meth)acrylates [33,34,[39][40][41][42][43][44], phenol derivatives [45,46], fumarates [47,48], dienes [49,50], halo-olefins [51][52][53], and other non-commercial ones [54][55][56][57][58][59][60][61] in water, solubilized by CD, via free radical polymerization methods. During the polymerization, the CD, every time, slips off from the last monomeric unit of the polymer, and the product precipitates, resulting in a pure product, or simple purification.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] The kinetic investigation of some acrylic monomers revealed that, upon increasing the hydrophobicity of the monomer, the polymerization rates increase. [14,15] Generally, the RAMEB dissociates from the growing chain step by step.…”
Section: Introductionmentioning
confidence: 99%
“…The free-radical [5][6][7][8][9][10][11][12][13][14][15] and controlled 'living' [16] polymerizations of various CD-complexed vinyl derivatives and also some other types of monomers in water have recently been investigated. The synthesis of electrical conducting polymers from aqueous media via oxidative coupling have also been described, [17,18] and some kinetics of the homoand copolymerization of several kinds of CD-complexed monomers in aqueous medium have been studied.…”
Section: Introductionmentioning
confidence: 99%